DEVENIR DES MACRO-AMPUTES TRAUMATIQUES DU MEMBRE THORACIQUE : CAS D’UN PAYS EN DEVELOPPEMENT - A, Walla; K, Amakoutou; E Y, James; G, Ayouba; B, Bakriga; A, Abalo; A M, Dossim (European Scientific Journal, ESJ, 2015)
Major upper limb trauma are rare lesions that management should be done in a specialized center. Faced with complex trauma of the upper limb, the orthopedist wonders if everything must be done to maintain a sometimes very functional upper limb amputated. We report the case of three male patients aged 18, 26 and 30 years of crash victims of upper limb accidents from the public road and work. The dominant member was diagnosed in a patient. Two patients underwent arm amputation stump and regularization forearm was performed in the third. Infection of amputation stump with surgery to stabilize, was recorded in a patient. One had a prosthesis made on the spot with his socio-professional reintegration, other patients are waiting.